A novel stromal lncRNA signature reprograms fibroblasts to promote the growth of oral squamous cell carcinoma via LncRNA-CAF/interleukin-33. (13th January 2018) - Ding, Liang; Ren, Jing; Zhang, Dongya; Li, Yi; Huang, Xiaofeng; Hu, Qingang; Wang, Hui; Song, Yuxian; Ni, Yanhong; Hou, Yayi
Abstract: Stromal carcinoma-related fibroblasts (CAFs) are the main type of non-immune cells in the tumor microenvironment (TME). CAFs interact with cancer cells to promote tumor proliferation. Long non-coding RNAs (lncRNAs) are known to regulate cell growth, apoptosis and metastasis of cancer cells, but their role in stromal cells is unclear. Using RNA sequencing, we identified a stromal lncRNA signature during the transformation of CAFs from normal fibroblasts (NFs) in oral squamous cell carcinoma (OSCC). We uncovered an uncharacterized lncRNA, FLJ22447, which was remarkably up-regulated in CAFs, referred to LncRNA-CAF (Lnc-CAF) hereafter. Interleukin-33 (IL-33) was mainly located in the stroma and positively co-expressed with Lnc-CAF to elevate the expression of CAF markers (α-SMA, vimentin and N-cadherin) in fibroblasts. In a co-culture system, IL-33 knockdown impaired Lnc-CAF-mediated stromal fibroblast activation, leading to decreased proliferation of tumor cells. Mechanistically, Lnc-CAF up-regulated IL-33 levels and prevented p62-dependent autophagy–lysosome degradation of IL-33, which was independent of LncRNA-protein scaffold effects. Treatment with the autophagy inducer, rapamycin, impaired the proliferative effect of Lnc-CAF/IL-33 by promoting IL-33 degradation. In turn, tumor cells further increased Lnc-CAF levels in stromal fibroblasts via exosomal Lnc-CAF. In patients with OSCC, high Lnc-CAF/IL-33 expression correlated with high TNM stage ( n = 140). Moreover, high Lnc-CAF expression predicted poor prognosis. In vivo, Lnc-CAF knockdown restricted tumor growth and was associated with decreased Ki-67 expression and α-SMA + CAF in the stroma. In conclusion, we identified a stromal lncRNA signature, which reprograms NFs to CAFs via Lnc-CAF/IL-33 and promotes OSCC development. Abstract : We here, for the first time, reported the long non-coding RNAs (lncRNAs) profile of stromal fibroblasts in oral squamous cell carcinoma (OSCC) and unveiled a novel LncRNA-CAF as an important molecule reprogramming CAFs via IL-33 to support OSCC growth.